Analisis Lirik Lagu Daerah Banjar “Paris Barantai” karya H. Anang Ardiansyah - Siti Mutiah; Dwi Wahyu Candra Dewi (BLAZE : Jurnal Bahasa dan Sastra dalam Pendidikan Linguistik dan Pengembangan, 2025)
This article examines the Banjar folk song entitled "Paris Barantai," which is a work of H. Anang Ardiansyah and has been rearranged by Ken Steven. This song raises the theme of love and deep longing for one's hometown and loved ones, while also depicting the natural beauty of Kotabaru, South Kalimantan. This study applies a qualitative method with a literature study approach, aiming to analyze the social and cultural values contained in the song and their influence on the identity of the Banjar community. The results of the study show that the song "Paris Barantai" contains various life values, such as mutual cooperation, kinship, religiosity, loyalty, and respect for culture and the environment. Furthermore, this song functions as a means of preserving the Banjar language and as a medium for disseminating the moral and cultural values of the Banjar community. As one of the regional musical works, "Paris Barantai" not only serves as entertainment, but also as a symbol of identity and cultural expression that strengthens social solidarity and introduces the richness of local culture to the national level.